Determining the feasibility and preliminary efficacy of a stroke instructional and educational DVD in a multinational context: a randomized controlled pilot study. (August 2018) - Jones, Kelly M; Bhattacharjee, Rohit; Krishnamurthi, Rita; Blanton, Sarah; Barker-Collo, Suzanne; Theadom, Alice; Thrift, Amanda G; Wolf, Steven L; Venketasubramanian, Narayanaswamy; Parmar, Priya; Maujean, Annick; Ranta, Annemarei; et al.
Objective: To assess the feasibility of conducting a randomized controlled trial of an instructional and educational stroke DVD and determine the feasibility and preliminary efficacy of this intervention in a multinational context. Design: Non-funded, pilot randomized controlled trial of intervention versus usual care. Setting: International, multicentre, community-based. Participants: Community-living adults up to three years post stroke with moderate to severe disability and their nominated informal caregivers. Interventions: Intervention patients viewed and practised rehabilitation techniques demonstrated in the DVD over six weeks. Main measures: Trial feasibility by number of active recruitment sites, recruitment efficiency, randomization and follow-up. Intervention feasibility by patient and caregiver impressions. Preliminary efficacy by the quality of life – 5-level EuroQol-5D (EQ-5D) health status measure, General Health Questionnaire and Centre for Epidemiological Studies–Depression at two months. Results: In total, 14 recruitment sites were established across eight countries. Recruitment was achieved at nine (64%) sites. Over 16 months, 66 participants were recruited (mean (SD) age = 63.5 (12.47) years) and randomized to intervention ( n  = 34) and control ( n  = 32) groups. In total, 54 (82%) completed a follow-up assessment. Patient and/or caregiver comments about the benefits and barriers to accessing the intervention were mixed. There were no significant between-group differences in outcomes at two months ( P  > 0.05). Conclusion: Conducting a multinational trial of a stroke DVD requires full funding. The intervention was acceptable to some patients and their caregivers, yet a generalized education approach did not fully meet their needs and/or expectations. A more individualized method may be required to meet peoples' changing needs during stroke recovery.